Influence of Composite C-S-H Seed Prepared by Wet Grinding on High-Volume Fly Ash Concrete - Shiheng Wang; Jianan Liu; Yaogang Tian; Peng Zhao (Buildings)
In order to reduce the production cost of preparing C-S-H seeds (C-seeds) by wet grinding cement, this paper prepares a composite C-seed by mixing cement and silica fume (SF) in six proportions. Adding the C-seed to high-volume fly ash (FA) concrete would improve the insufficient early strength of this type of concrete. The properties of different C-seeds, as well as their effects on the mechanical properties, hydration characteristics and microstructure of concrete, were assayed by XRD, SEM and TG. As the results show, silica fume can contribute to the formation of the C-seed by promoting the hydration of cement. As the ratio of cement to silica fume (C/S) decreases, the particle size of the C-seed gradually decreases, the volume of CH decreases and the volume of C-S-H increases first, but when the C/S is less than 4/6, it decreases significantly. After the composite C-seed was added, the compressive strength (CS) of concrete at 1 d and 28 d was significantly improved. The CS at 1 d decreased following the decrease in the C/S ratio; however, it increased at 28 d. As the C/S ratio decreased, the porosity of the concrete with added C-seed decreased at 28 d, making the structure denser. The XRD, NMR and TG results show that C-seeds with C/S values greater than 4:6 have a more pronounced effect on promoting the hydration of cement.